2014
DOI: 10.1002/hed.23392
|View full text |Cite
|
Sign up to set email alerts
|

New device for single-stage in-office secondary tracheoesophageal puncture: Animal studies

Abstract: We believe the MAID can facilitate single-stage office-based secondary TEP in postlaryngectomy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In contrast, in a group of 58 patients with cT1/T2 parotid gland carcinoma analysed by Stenner et al, cervical occult metastases (without intra/periparotid) were found in only 5.1% of patients [3]. Among all presented series, only in the material by Lau et al, there was no statistical significance detected for variables associated with local stage [14]. Patients’ age turned out to be a significant clinical risk factor in three series and male sex in one series [2, 5, 13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, in a group of 58 patients with cT1/T2 parotid gland carcinoma analysed by Stenner et al, cervical occult metastases (without intra/periparotid) were found in only 5.1% of patients [3]. Among all presented series, only in the material by Lau et al, there was no statistical significance detected for variables associated with local stage [14]. Patients’ age turned out to be a significant clinical risk factor in three series and male sex in one series [2, 5, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the own material and literature (Table 3), it is obvious that the most important statistically significant risk factors for metastases to cervical lymph nodes are grade (7/10 series) and local stage: T (6/10) and its indicators, i.e. the size of the tumour (2/10), extraglandular infiltration (4/10) and nerve VII paresis (4/10) [2, 4, 5, 7, 1014]. In the presented material, there was a high proportion of occult metastases observed (30%) and even though we did not observe statistical significance for T, in a uni- and multivariate analysis, we showed a significant effect of extraparotid extension, which in TNM classification appears in T3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Lim et al [22] might have been the first to find that compared to patients without IPN metastasis, patients with a cN0 neck with IPN metastasis are more likely to develop locoregional recurrence. In a study published by Klussmann et al [23], univariate analysis revealed IPN involvement as an additional significant risk factor of tumour recurrence in 55 patients with pN+ tumours. Nisa et al [24] reported that decreased disease-free survival could be expected in patients with IPN involvement.…”
Section: Discussionmentioning
confidence: 99%